Anatomy of Left Inferior Phrenic Vein in Patients Without Portal Hypertension - Araki, Takuji; Imaizumi, Akira; Okada, Hiroki; Sasaki, Yu; Onishi, Hiroshi (American journal of roentgenology (1976), 2021)
OBJECTIVE. The left inferior phrenic vein (LIPV) can be an origin of a gastrorenal shunt from gastric varices. The purpose of our study was to evaluate the angiographic anatomy of the LIPV, particularly anastomoses of the LIPV with the portal vein (PV). SUBJECTS AND METHODS. Of 240 patients with primary aldosteronism who underwent adrenal venous sampling from April 2011 to July 2019, 236 had normal liver and renal function and were included in this study. Of those patients, 214 had evaluable LIPV venography. The angiographic anatomy of the LIPV was classified as type 1 when the subdiaphragmatic transverse part of the LIPV could be visualized or as type 2 when it could not. Type 1 was subclassified into type 1a, which was defined as the transverse part of the LIPV connected with a single vein, or type 1b, which was defined as the transverse part of the LIPV connected with several veins via anastomoses. Type 2 LIPVs were subclassified into type 2a, in which the LIPV had an undeveloped vertical part; type 2b, in which the LIPV had backflow into systemic veins; or type 2c, in which the LIPV had a connection to the PV. The presence of an anastomosis with the PV was defined as the PV being visualizable on LIPV venography. RESULTS. Assessment of LIPV venography revealed type 1 in 71.5% (153/214) of patients, including type 1a (22.4%, 48/214) and type 1b (49.1%, 105/214). Type 2 LIPVs were observed in 28.5% (61/214) of patients, including types 2a (6.5%, 14/214), 2b (11.2%, 24/214), and 2c (10.7%, 23/214). An anastomosis of the LIPV with the PV was found in 28.0% (60/214) of patients, including 10.7% (23/214) with type 2c and 17.3% (37/214) with type 1 with a visible PV. The anastomoses of the LIPV with the PV were of various sizes. CONCLUSION. The angiographic anatomy of the LIPV varied and was commonly formed from several veins connected by anastomoses. An anastomosis between the LIPV and PV, which might be the origin of gastric varices, was found in 28.0% of patients.OBJECTIVE. The left inferior phrenic vein (LIPV) can be an origin of a gastrorenal shunt from gastric varices. The purpose of our study was to evaluate the angiographic anatomy of the LIPV, particularly anastomoses of the LIPV with the portal vein (PV). SUBJECTS AND METHODS. Of 240 patients with primary aldosteronism who underwent adrenal venous sampling from April 2011 to July 2019, 236 had normal liver and renal function and were included in this study. Of those patients, 214 had evaluable LIPV venography. The angiographic anatomy of the LIPV was classified as type 1 when the subdiaphragmatic transverse part of the LIPV could be visualized or as type 2 when it could not. Type 1 was subclassified into type 1a, which was defined as the transverse part of the LIPV connected with a single vein, or type 1b, which was defined as the transverse part of the LIPV connected with several veins via anastomoses. Type 2 LIPVs were subclassified into type 2a, in which the LIPV had an undeveloped vertical part; type 2b, in which the LIPV had backflow into systemic veins; or type 2c, in which the LIPV had a connection to the PV. The presence of an anastomosis with the PV was defined as the PV being visualizable on LIPV venography. RESULTS. Assessment of LIPV venography revealed type 1 in 71.5% (153/214) of patients, including type 1a (22.4%, 48/214) and type 1b (49.1%, 105/214). Type 2 LIPVs were observed in 28.5% (61/214) of patients, including types 2a (6.5%, 14/214), 2b (11.2%, 24/214), and 2c (10.7%, 23/214). An anastomosis of the LIPV with the PV was found in 28.0% (60/214) of patients, including 10.7% (23/214) with type 2c and 17.3% (37/214) with type 1 with a visible PV. The anastomoses of the LIPV with the PV were of various sizes. CONCLUSION. The angiographic anatomy of the LIPV varied and was commonly formed from several veins connected by anastomoses. An anastomosis between the LIPV and PV, which might be the origin of gastric varices, was found in 28.0% of patients.